A Place in History? The 2018 Marx Bicentennial in Germany. Issue 3 (1st December 2020) - Mares, Detlev
Abstract : This article queries the merits and limitations of the historicization approach that informed many of the productions on Marx's two-hundredth anniversary in Germany in 2018. The article presents the approach's application in exhibitions, biographies, and movies. In order to contextualize the historicization project in the discussions surrounding Marx in Germany, a framework for assessing the approach is provided by a close reading of the discussions related to monuments erected to Marx, with special attention given to a new statue in his birthplace, Trier.